PRODUKTIVITAS KERJA PEGAWAI DINILAI DARI PERSPEKTIF KETERAMPILAN KERJA, PENGALAMAN KERJA, SIKAP KERJA, DAN PRESTASI KERJA DI LEMBAGA PERKREDITAN DESA (LPD) SE-KEC. BULELENG: KADEK BUDA MARIANI, LUH KARTIKA NINGSIH - Mariani, Kadek Buda; Ningsih, Luh Kartika (Komunitas Manajemen Kompetitif, 2023)
Productivity in the world of work is very important, because with workproductivity it is expected that work will be carried out effectively and efficiently. This studyaims to determine the work productivity of employees assessed from the perspective of skills,experience, attitudes and work performance at the Village Credit Institution (LPD) Se.district. Buleleng. The population in this study was 100 employees and used a saturatedsample technique so that the number of samples was 100 employees. Based on the results ofthe study, the results obtained that work skills had a positive and significant effect on workperformance of 0.306. Work Skills have a significant and positive effect on work productivityof 0.259. Work experience has a positive and significant effect on work performance of 0.485.Work Experience has a positive and significant effect on Work Productivity of 0.267. WorkAttitude has a positive and significant effect on work performance of 0.172. Work Attitudehas a negative effect on Work Productivity of -0.184 so it is rejected. Work Performance issignificant and has a positive effect on Work Productivity of 0.52